Host-parasite interactions during Plasmodium infection: Implications for immunotherapies - Chandley, Pankaj; Ranjan, Ravikant; Kumar, Sudhir; Rohatgi, Soma (Frontiers in Immunology, 2023)
Malaria is a global infectious disease that remains a leading cause of morbidity and mortality in the developing world. Multiple environmental and host and parasite factors govern the clinical outcomes of malaria. The host immune response against the Plasmodium parasite is heterogenous and stage-specific both in the human host and mosquito vector. The Plasmodium parasite virulence is predominantly associated with its ability to evade the host’s immune response. Despite the availability of drug-based therapies, Plasmodium parasites can acquire drug resistance due to high antigenic variations and allelic polymorphisms. The lack of licensed vaccines against Plasmodium infection necessitates the development of effective, safe and successful therapeutics. To design an effective vaccine, it is important to study the immune evasion strategies and stage-specific Plasmodium proteins, which are targets of the host immune response. This review provides an overview of the host immune defense mechanisms and parasite immune evasion strategies during Plasmodium infection. Furthermore, we also summarize and discuss the current progress in various anti-malarial vaccine approaches, along with antibody-based therapy involving monoclonal antibodies, and research advancements in host-directed therapy, which can together open new avenues for developing novel immunotherapies against malaria infection and transmission.